2014
DOI: 10.7763/ijtef.2014.v5.350
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Safety Training Practices on Organizational Safety Performance: An Evidence in Malaysia’s Automotive Industry

Abstract: Abstract-This paper aims to investigate the role of safety training practices to safety performance in Malaysia's automotive industry. This study adopts a non-experimental type research which employs questionnaire as the method of collecting data. The measurement tool undertaken in the data collection is Safety Performance Scale that developed by Wu et al. (2007). A total of 696 employees from Malaysia automotive manufacturing and assembly plants are selected as the respondents of this study. The selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…They exhibited extensive knowledge on the types of occupational hazards, safety measures, required PPEs and had received training on accident prevention and on how to use PPEs. These results are consistent with the findings of Wahab et al (2014) who found that training workers on performance management of safety practices is important across companies and industries. Safety measures, however, cannot completely contribute to total prevention unless they are tied to problems relevant to individuals.…”
Section: Analyses and Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…They exhibited extensive knowledge on the types of occupational hazards, safety measures, required PPEs and had received training on accident prevention and on how to use PPEs. These results are consistent with the findings of Wahab et al (2014) who found that training workers on performance management of safety practices is important across companies and industries. Safety measures, however, cannot completely contribute to total prevention unless they are tied to problems relevant to individuals.…”
Section: Analyses and Discussion Of Resultssupporting
confidence: 92%
“…Successful investment in employee health and safety protection increases engagement, organizational efficiency and the company’s overall performance (Sembe and Ayuo, 2017; Quaigrain and Issa, 2021). In Malaysia, Wahab et al (2014) claimed that training workers on performance management safety practices is vitally important in every company and industry. Safety measures, however, cannot fully contribute to satisfaction unless they address problems relevant to the individual worker.…”
Section: Theorizing Employees’ Knowledge and Attitude Toward Occupati...mentioning
confidence: 99%
“…Employee participation and training have a significant positive impact on safety performance (Setyawan et al, 2021). Similarly, Wahab et al (2014)'s findings show that safety training practises have a significant impact on an organization's safety performance. Sukamani, Wang & Kusi (2021) had shown how safety training moderated the relation between safety worker behaviour & safety performance.…”
Section: Safety Management Practicesmentioning
confidence: 93%
“…Providing training should promote action, stimulate sensitivity, increase knowledge, and help workers deepen their knowledge and skills (O. Alli, 2008). In addition to aiming to increase knowledge, training for workers can also be a place to promote and communicate information and expectations related to the implementation of K3 to workers, which is stated by Wahab et al (2014) in his research. Moreover, in the study, it was also stated that providing training to workers can affect the improvement of OSH performance in the workplace (Wahab et al, 2014).…”
Section: Trainingmentioning
confidence: 99%